Effect of the Ti-target arc current on the properties of Ti-doped ZnO thin films prepared by dual-target cathodic arc plasma deposition. Issue 13 (October 2016) - Hsu, Shuo-Fu; Weng, Min-Hang; Chou, Jyh-Horng; Fang, Chun-Hsiung; Yang, Ru-Yuan
Abstract: Ti-doped zinc oxide (Ti:ZnO) films were prepared on glass substrates using the dual-targets cathodic arc plasma deposition process. The effect of the arc current of the Ti target (30, 40, 50 and 60 A) on structural, optical and electrical properties of the deposited films was investigated. All the prepared films exhibited a preferred (002) orientation with the c-axis perpendicular to the substrate, and the intensity of (0 0 2) peak was decreased as increasing the arc current of the Ti target. Zn, Ti and O elements were detected in the deposited film, showing that Ti:ZnO film was successfully deposited. All Ti:ZnO films showed an average transmittance of over 84% in the visible region and the calculated values of the band gap were about 3.22 eV. Under an arc current of Ti target of 30 A, the deposited Ti:ZnO film had the lowest resistivity of 7.9 × 10 −3  Ω cm.